Informational leadership of rubber futures market in India: exploration using data with different temporalities - P Narayanan; T K Sebastian (Agricultural Economics Research Review, 2023)
The informational efficiency of a commodity futures market is critical in determining resource allocation; an unbiased futures market that leads in information assimilation is considered efficient. Using the daily and monthly forecast series data on rubber futures trading, the informational efficiency of the National Multi Commodity Exchange is investigated. The results obtained from the two datasets are contradictory because of ‘pseudo price discovery’ in the futures market. The futures price is found to be highly dependent on the prevailing spot price; therefore, forecasts of future spot prices should be based on the prevailing spot price.